Ciencia y política en los proyectos de obras públicas del Consulado de Cartagena de Indias, 1795-1810 - Lucena Giraldo, Manuel (Pontificia Universidad Javeriana, 2014)
This article analizes, characterizes and contextualizes the establishment of the "Consulado de Comerciantes" of Cartagena in 1795. The Consulate is interpreted as an "axis of power" during New Granada's Independence struggle. The autor studies the Consulate from the perspective of political geography and establishes, in a parallel fashion, a relationship between science and policy. The public works projects of Cartagena, with clear regional priorities, clashed with the projects of the commercial and scientific class in the capital, Santafé de Bogotá. The article is based on the published informe (report) of the Consulate at Cartagena, which dealt with the healt of the colonial economy in the Vice Royalty.